OPTIMALISASI E-COMMERCE UNTUK PENGEMBANGAN EKONOMI KREATIF DI ERA DIGITAL - Wahyu Nofiyan Hadi (ABDISUCI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The development of digital technology has driven significant changes in product marketing and distribution patterns, including in the Micro, Small, and Medium Enterprises (MSMEs) sector. However, most MSMEs still face limitations in optimally utilizing e-commerce platforms. This community service activity aims to optimize the use of e-commerce to support the development of the creative economy among MSMEs in Sumbertaman Village, Probolinggo City. The activity implementation methods include initial observation, outreach, training, and mentoring on the use of e-commerce platforms and digital marketing. The results of the activity indicate an increase in understanding and skills of MSMEs in managing online stores, creating attractive product content, and utilizing digital marketing features to expand market reach. This e-commerce optimization has a positive impact on increasing product visibility and sales opportunities for MSMEs. This activity is expected to become a model for sustainable digital technology-based MSME empowerment in supporting the growth of the creative economy in the digital era.